2022
DOI: 10.3390/ijms232214146
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiling in Different SARS-CoV-2 Genetic Variants

Abstract: This study is a successor of our previous work concerning changes in the chemokine profile in infection that are associated with different SARS-CoV-2 genetic variants. The goal of our study was to take into account both the virus and the host immune system by assessing concentrations of cytokines in patients infected with different SARS-CoV-2 variants (ancestral Wuhan strain, Alpha, Delta and Omicron). Our study was performed on 340 biological samples taken from COVID-19 patients and healthy donors in the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 70 publications
(77 reference statements)
3
14
1
Order By: Relevance
“…To the best of our knowledge, this study was the first to report the use of tocilizumab in a large cohort of severe COVID-19 patients infected with the delta and omicron VOC, suggesting that, among the patients developing a severe form of the disease, the mortality rates were similar in the omicron and delta cases, as it has been reported with previous VOCs [14]. In the same line, some authors have highlighted that the rate of severe COVID-19 may change depending on the VOC, but, in cases of severe forms, they reported that the cytokine secretion remained stable and independent from the VOC [22]. Accordingly, our results suggested that tocilizumab remained an efficient option for the treatment of severe COVID-19 patients in association with corticosteroids, regardless of the VOC involved.…”
Section: Discussionsupporting
confidence: 60%
“…To the best of our knowledge, this study was the first to report the use of tocilizumab in a large cohort of severe COVID-19 patients infected with the delta and omicron VOC, suggesting that, among the patients developing a severe form of the disease, the mortality rates were similar in the omicron and delta cases, as it has been reported with previous VOCs [14]. In the same line, some authors have highlighted that the rate of severe COVID-19 may change depending on the VOC, but, in cases of severe forms, they reported that the cytokine secretion remained stable and independent from the VOC [22]. Accordingly, our results suggested that tocilizumab remained an efficient option for the treatment of severe COVID-19 patients in association with corticosteroids, regardless of the VOC involved.…”
Section: Discussionsupporting
confidence: 60%
“…The frequency of the GG genotype was higher in mild than in severe COVID-19 individuals, according to a study on the Mexican population. However, the results were not determined to be statistically significant [18,20]. The IL10 rs1800872 GT genotypes were linked to a higher risk of contracting the influenza A/H3N2 virus.…”
Section: Discussionmentioning
confidence: 84%
“…These polymorphisms are a member of a collection of haplotypes linked to various amounts of IL10 production [18,19]. In a study has been shown that Omicron variant showed lower IL-10 concentrations compared to other variants, a notion that can potentially be explained by clinical features of this specific variant [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also found increased secretion of proinflammatory cytokines such as CCL20/MIP3ɑ, IL-10, IL-15, IL-27 in non-survivors than in controls. Increased secretion of CCL20/MIP3ɑ is a new finding in COVID-19, although we previously reported an increase in concentrations of other macrophage inflammatory proteins, CCL3/MIP-1a and CCL4/MIP-1b [30]. CCL20/MIP3ɑ mainly elicits its effector function via CCR6 receptor binding; interestingly enough, we previously noted a negative correlation between CCR6 ex-pressing CD8+ cells and IL-27 [31].…”
Section: Discussionmentioning
confidence: 85%